1990
DOI: 10.1111/j.1600-079x.1990.tb00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of the Dog Pineal Gland: Electron Microscopy

Abstract: The ultrastructure of the dog pineal gland from the first postnatal day to the seventh month is described. In the first postnatal stages, pineal parenchyma only shows immature proliferative cells with abundant cytoplasmic glycogen. Nerve fibers are seen in the pineal connective tissue spaces. The differentiation of the dog pineal cell types begins in the first postnatal week. Both pinealocytes and pigmented cells are first seen on the fourth postnatal day. The pineal astrocytes are observed on the tenth day. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0
5

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 14 publications
8
40
0
5
Order By: Relevance
“…The pineal size was generally larger in puppies after eyelids separation with more developed cell processes. In support to our results, a gradual increase in the pineal gland size was noticed in neonatal puppies (Calvo et al, 1988(Calvo et al, , 1990. Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pineal size was generally larger in puppies after eyelids separation with more developed cell processes. In support to our results, a gradual increase in the pineal gland size was noticed in neonatal puppies (Calvo et al, 1988(Calvo et al, , 1990. Fig.…”
Section: Discussionsupporting
confidence: 91%
“…accordance, it has previously been shown that before eyelids separation, the puppies pinealocytes in the first 14 days of the postnatal life and those of rabbit in the first 24 h of postnatal life were immature cells (Calvo et al, 1988(Calvo et al, , 1990. On the other hand, after eyelids separation at the age of 25 days in puppies, the pineal cells become differentiated into mature pinealocytes and astrocytes.…”
Section: Discussionmentioning
confidence: 93%
“…The human embryonic pineal gland exhibits two distinctive types of cells, a photoreceptor cell and a neuroendocrine cell eventually transforming into a melatonin-secreting pinealocyte (5). At the end of the third month of life, the photoreceptor cell type begins to lose its structure and finally vanishes during the fifth month (25). The size of the pineal gland is also affected by the season.…”
Section: Discussionmentioning
confidence: 99%
“…Características muy semejantes en cuanto a organización arquitectural observaron Calvo et al (1990) en la pineal de perro adulto, a la cual describieron en forma de pera con una amplia zona proximal y una delgada parte distal. La parte dorsal de la glándula también aparece revestida por una capa de células ciliadas.…”
Section: Histología De La Glándula Pinealunclassified